THE ANATOMICAL STUDY OF THE SUPERFICIAL BRANCHES OF FEMORAL ARTERY IN FEMORAL TRIANGLE - Dr. MANJAPPA T; Dr. RAGHAVENDRA V.P. (International Journal of Pharma and Bio Sciences, 2012)
The perfect knowledge of anatomy of superficial branches of femoral artery has profound importance for creation of successful flaps and in vulvar reconstruction. In this study we conducted a quantitative study of superficial external pudendal, superficial epigastric and superficial circumflex iliac arteries as the basis of skin grafts. Present study was undertaken on 20 properly embalmed cadavers. Twenty right and twenty left side femoral triangle of cadavers were dissected. The source of origin, side of origin and distance from the point of origin of the artery to mid inguinal point of all three arteries were noted. Superficial external pudendal artery arises generally from femoral artery with preponderance from medial aspect and in almost equal cases within 3 cm and between 3.1 – 6.0 from point of origin to midinguinal point. Superficial epigastric artery arises from femoral artery in all cases with preponderance from anterior aspect of femoral artery and in almost all cases within 3 cm from point of origin to mid inguinal point Superficial circumflex arises generally from femoral artery with preponderance from lateral aspect and in almost all cases within 3cm from the point of origin to mid inguinal point.